Neoliberal urban transformations in the arab city: Meta-narratives, urban disparities and the emergence of consumerist utopias and geographies of inequalities in Amman - Daher, Rami (Environnement urbain / Urban Environment, 2013)
This research represents a discursive-comparative analysis aiming to understand the current urban neoliberal condition in the Arab world in terms of the circulating patterns of urban transformation. The research introduces and suggests a discursive framework in which various neoliberal projects could be examined and evaluated against one or more of the following indicators: urban lifestyle, emancipatory neoliberal discourse, claims to social sustainability, socio-spatial politics and dynamics, governance and place management, changing role of the state, and circulation of neoliberal practices. The research applies and benefits from a reconciliation between neo-Marxist theories of political economy and poststructuralist approaches related to the art of governance. However, in doing so it relies mostly on one body of theory, namely, neo-Marxist theories considering neoliberalism as a class project of social exclusion. The framework of analysis is applied to the following three case studies in Amman: high-end business towers, gated upper-middle class communities, and low-income housing projects. In general, these projects, despite their emancipatory rhetoric, led to geographies of inequality and urban disparities within the city of Amman.